Pervious concrete: The art of improving strength properties - Rostam, N. E.; Putra Jaya, Ramadhansyah; Md Rizal, Othman; Zack, L. E. H.; Mohd Haziman, W. I. (IOP Science, 2021)
Urban cities in Malaysia are highly vulnerable to flash floods due to improper drainage system and the impermeable road surface. The Pervious Concrete (PC) Pavement for urban water management indicates the implementation of this system shows promising results to reduce flash flood volume and among the mitigation that can be applied is by adopting the permeable pavement systems. This was based on a case study of Sponge City in China. Since the properties normally consist of coarse aggregate only / or less fine aggregate to fill in the void structure. Regardless of the high advantage of these systems to reduce the flooding impact, this permeable pavement is known for its lower strength. Due to this fact, it is rare and impossible for this permeable pavement to be utilized at the main road and highway. Whereas, currently in Malaysia, the permeable concrete is only accustomed to light traffic loadings such as walkways and car park. This paper was discussing the way to improve the strength properties of PC pavements with a focus on sustainable development.